Pelatihan Intensif Kader Kesehatan Sebagai Upaya Pencegahan Stunting Yang Efektif - Iskandar Munir (Jurnal Ilmu Kesehatan dan Gizi, 2024)
Stunting is a chronic nutritional problem that impacts the growth and development of children, posing a serious challenge to public health in Indonesia. One strategic approach to addressing this issue is through intensive training of health cadres. Health cadres play a crucial role in educating the community about the importance of balanced nutrition and good health practices, especially for pregnant women and young children. Structured and continuous intensive training for health cadres is expected to enhance their knowledge and skills in early detection of stunting cases, providing nutritional education, and implementing appropriate interventions. This training program covers various topics such as healthy eating patterns, infant and young child feeding (IYCF), and prevention of diseases contributing to stunting. Additionally, the training includes simulations and field practices that allow health cadres to apply their acquired knowledge in real-life situations. Results from this training show significant improvements in the competencies of health cadres and a reduction in stunting prevalence in the intervention areas. Therefore, intensive training of health cadres has proven to be an effective strategy for stunting prevention and needs to be widely implemented in various regions of Indonesia.